2021
DOI: 10.3390/cells10113223
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free DNA Variant Sequencing Using Plasma and AR-V7 Testing of Circulating Tumor Cells in Prostate Cancer Patients

Abstract: Prostate cancer (PCa) is the second most common malignant cancer and is a major cause of morbidity and mortality among men worldwide. There is still an urgent need for biomarkers applicable for diagnosis, prognosis, therapy prediction, or therapy monitoring in PCa. Liquid biopsies, including cell-free DNA (cfDNA) and circulating tumor cells (CTCs), are a valuable source for studying such biomarkers and are minimally invasive. In our study, we investigated the cfDNA of 34 progressive PCa patients, via targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…After stratifying the patients at the median of affected DDR genes with CPS variants (>4 vs. ≤4), those with >4 affected DDR genes with CPS variants showed a shorter TTC compared to patients with fewer DDR genes with CPS variants. This finding agreed with our previous result that patients with a higher number of gene variants have a shorter TTC in general [ 34 ]. We evaluated the association of gene variants in each DDR gene with OS or DSS, and we found that patients with gene variants in some DDR genes showed a better OS or DSS than patients without such gene variants.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…After stratifying the patients at the median of affected DDR genes with CPS variants (>4 vs. ≤4), those with >4 affected DDR genes with CPS variants showed a shorter TTC compared to patients with fewer DDR genes with CPS variants. This finding agreed with our previous result that patients with a higher number of gene variants have a shorter TTC in general [ 34 ]. We evaluated the association of gene variants in each DDR gene with OS or DSS, and we found that patients with gene variants in some DDR genes showed a better OS or DSS than patients without such gene variants.…”
Section: Discussionsupporting
confidence: 94%
“…The cfDNA of 34 PCa patients (39 samples) was evaluated for gene variants in 99 genes by NGS as described previously [ 34 ] and here in Table S2 . We investigated in a continued analysis, gene variants in DNA damage repair genes and their association with prognosis, i.e., OS, DSS or TTC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation